Application of Electron‐Rich Covalent Organic Frameworks COF‐JLU25 for Photocatalytic Aerobic Oxidative Hydroxylation of Arylboronic Acids to Phenols. Issue 29 (25th March 2021) - Xiao, Guangjun; Li, Wenqian; Chen, Tao; Hu, Wei‐Bo; Yang, Hui; Liu, Yahu A.; Wen, Ke
Abstract: Visible‐light‐driven organic reactions are environmentally friendly green chemical transformations among which photosynthetic oxidative hydroxylation of arylboronic acids to phenols has attracted increasing research interest during the very recent years. Given the efficiency and reusability of heterogeneous catalysts, COF‐JLU25, an electron‐rich COF‐ based photocatalyst constructed by integrating electron‐donating blocks 1, 3, 6, 8‐tetrakis(4‐aminophenyl)pyrene (PyTA) and 4‐[4‐(4‐formylmethyl)‐2, 5‐dimethoxyphenyl] benzaldehyde (TpDA), was selected as a photocatalyst for the oxidative hydroxylation of arylboronic acids. In our studies, COF‐JLU25 demonstrated excellent photocatalytic activity with high efficiency, robust reusability, and low catalyst loading, showcasing an application potential of previously underexplored COF‐based photocatalyst composed solely of electron‐rich units. Abstract : COF‐JLU25, a COF‐ based photocatalyst comprised solely of electron‐donating units, 1, 3, 6, 8‐tetrakis(4‐aminophenyl)pyrene (PyTA) and 4‐[4‐(4‐formylmethyl)‐2, 5‐dimethoxyphenyl] benzaldehyde (TpDA), demonstrated excellent photocatalytic activity with high efficiency, robust reusability, and low catalyst loading when used in catalyzing the oxidative hydroxylation of arylboronic acids.